ANALISIS KINERJA PUTAR BALIK (U-TURN) (STUDI KASUS PUTAR BALIK (U- TURN) DI DEPAN RUMAH SAKIT UMUM PUSAT DR. MOHAMMAD HOSEIN (RSMH) YANG TERLETAK DI JALAN JENDRAL SUDIRMAN - Maharani, Pratiwi; Rosyad, Farlin; Syarifuddin, Achmad; Sari, Anggi Purnama (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
The rapid growth of motorized vehicles in Palembang City has significantly impacted traffic congestion, particularly at the U-Turn facility in front of Dr. Mohammad Hoesin General Hospital (RSMH) on Jendral Sudirman Street. This study aims to analyze the performance of the U-Turn at this location through field surveys and secondary data analysis. Primary data include traffic volume, vehicle speed, queue length, and side friction, while secondary data were obtained from relevant institutions. The analysis results show that the degree of saturation (DS) reached 1.32 for the RSMH direction and 1.27 for the LIA direction, both exceeding the PKJI 2023 recommended limit (DS ≤ 1.0). The level of service (LOS) was classified as F, with the lowest average speed of12.11 km/h and a queue length of up to 78 meters during the Monday morning peak hour. The main factors contributing to the performance decline include high vehicle volumes, side friction from illegal parking and drop-off activities, and limited median width. These findings highlight the need for traffic management interventions such as controlling side friction, widening the median, or implementing signalized U-Turns to improve traffic flow efficiency.Keywords: traffic performance, U-Turn, degree of saturation, queue length, level of service